Preparation and application of Ni(ii) ion-imprinted silica gel polymer for selective separation of Ni(ii) from aqueous solution. Issue 25 (7th March 2017) - He, Hongxing; Gan, Qiang; Feng, Changgen
Abstract : A novel Ni(ii ) ion-imprinted sulfonate functionalized silica gel polymer was prepared with the surface imprinting technique for selective seperation of Ni(ii ) from aqueous solution. Abstract : In the present study, a novel Ni(ii ) ion-imprinted sulfonate functionalized silica gel polymer was prepared with the surface imprinting technique by using nickel(ii ) as the template ion, grafted silica gel as the support, and 2-acrylamido-2-methyl-1-propanesulfonic acid (AMPS) and ethylene glycol dimethacrylate (EGDMA) as the functional monomer and crosslinker, respectively. The sorbent was characterized by FT-IR, SEM, EDX, TG and BET. Kinetics studies indicated that the adsorption equilibrium was achieved within 12 min and the adsorption kinetics followed the pseudo-second-order rate equation. The adsorption isotherm was well fitted by the Langmuir model. The Ni(ii ) ion-imprinted silica gel polymer (Ni(ii )-IIP) exhibited a higher adsorption capacity and selectivity for Ni(ii ) in comparison to the non-imprinted silica gel polymer (Ni(ii )-NIP). The maximum adsorption capacities of Ni(ii )-IIP and Ni(ii )-NIP for Ni(ii ) were 20.30 and 4.87 mg g −1, respectively. The relative selectivity coefficients of the adsorbent for Ni(ii ) in the presence of Co(ii ), Cu(ii ), Zn(ii ) and Pb(ii ) were 4.09, 3.62, 5.78 and 5.86, respectively. Reusability studies indicated that the adsorption capacity of the prepared sorbent did not decrease significantly after repeated use six times. The precision of this method was verified and the prepared sorbent can be considered to be a promising sorbent for selective separation of Ni(ii ) from natural water samples.